Mengenal Inner Child: Jejak Masa Lalu Yang Membentuk Kepribadian - Nopi Nopita Sari; Irsyad Bagus Satria; Riski Tri Fauzan; Hidayani Syam (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Humans are complex beings shaped by various factors, including past experiences. One of the most influential aspects in personality formation is the inner child, which is the part of ourselves that stores memories, emotions, and childhood experiences. The inner child can affect our behavior, emotions, and relationships with others. Therefore, understanding the inner child is crucial for self-understanding and improving quality of life. This study aims to explore the concept of the inner child and its impact on personality. This study uses a literature review approach. The results show that the inner child is a part of oneself that stores memories, feelings, and childhood experiences that influence personality and behavior in adulthood. The inner child can be wounded due to traumatic experiences or unsupportive parenting, affecting emotional stability, social relationships, and self-confidence. Healing the inner child can be done through writing, self-reflection, and Ho’oponopono therapy. The benefits of healing the inner child include increased self-awareness, emotional healing, improved relationships with oneself and others, and increased self-confidence and courage.